PARENTAL SMOKING BEHAVIOR AND UNDERWEIGHT AMONG CHILDREN AGED 5-12 YEARS: EVIDENCE FROM RISKESDAS 2018 - Engelina, Bunga Ellen; Sufyan, Dian Luthfiana; Simanungkalit, Sintha Fransiske; Wahyuningsih, Utami (Fakultas Kesehatan Masyarakat, Universitas Jember, 2024)
In recent years, underweight remains a medium public health problem in Indonesia, despite the substantial decrease in prevalence, still, this long-standing issue are potentially altering children physical growth and cognitive development. This current study aims to investigate the association between parental smoking behavior and underweight in children by analyzing secondary data of the 2018 Indonesia Basic Health Research (RISKESDAS). A total sample of 39,451 children aged 5-12 years were analyzed in this study. Anthropometric measurement of body weight was obtained to identify underweight. A structure questionnaire was employed to obtained information on child sex (male or female), age (5-8 or 9-12), type of residence (urban or rural), parental age (under or older than 35), education (high: higher education graduate or under), working status (working or not working) and smoking behavior both among mother and father in the last one month. Among those who smoked, the average number of cigarettes being smoked was also questioned, as well as the experience of indoor smoking. Data were analyzed using SPSS version 25. There were 8.4% of underweight children in this study, 89.8% of parents were smoker, who 74.8% of them were father, on average smoked 14 cigarettes per day and 98.8% of them smoked inside the house. Underweight was not significantly associated with parental smoking behavior, type of residence, parental age and parental working status. Higher odds of being underweight was found among children age 5-8 years (OR 1.08, p = 0.04, 95% CI). While boys were protective factor against underweight (OR 0.75, p < 0.01, 95% CI). Despite no association found between parental smoking behavior and children underweight in current study, however, it remains relevant to remind parents that their smoking behavior, especially inside living space may hinder children physical growth and cognitive development.